C22-Ceramide Derived from Marine Microalgae Emiliania huxleyi Induces Melanosomal Autophagy via JNK/c-Jun Signaling Pathway in Mouse B16 Melanoma Cells - Jiyue Wan; Hui Ma; Yuxuan Xu; Shumiao Zhang; Jian Li; Guiling Li; Shiying Huang; Xiaotong Ye; Zhengxiao Zhang; Jingwen Liu (Journal of Ocean University of China, 2025)

Microwave-ultra-fast recovery of valuable metals from spent lithium-ion batteries by deep eutectic solvents - Ahui Zhu; Xinyu Bian; Weijiang Han; Yong Wen; Ke Ye; Guiling Wang; Jun Yan; Dianxue Cao; Kai Zhu; Shubin Wang (Waste Management, 2023)

Simulations of sea fog case impacted by air–sea interaction over South China Sea - Liguo Han; Shuqin Zhang; Feng Xu; Jingjing Lü; Zebin Lu; Guiling Ye; Siqi Chen; Jianjun Xu; Jiaming Du (Frontiers in Marine Science, 2022)
A sea fog event in the South China Sea was simulated using a coupled ocean–atmosphere model (WRF for the atmosphere and ROMS for the ocean). Offshore and onshore visibility, liquid water content, air temperature, humidity, and wind speed observations and MICAPS data were utilized to validate the model results. The results of the coupled model were also compared with those of the uncoupled atmosphere model. Sea fog duration in the coupled model was closer to offshore and onshore observations, but the uncoupled model emptily forecasted offshore fog, and underreported onshore fog. Air–sea temperature difference played an important role in regulating the formation and dissipation of sea fog. The decrease of sea surface temperature in the coupled model cooled the low-level atmosphere, promoted the condensation of low-level water vapor, and increased the low-level water vapor. The decrease of air–sea temperature difference strengthened the low-level stable stratification, which weakened the horizontal wind speed and favored the formation and development of sea fog. Rising wind speed was the major driver of fog dissipation.

Sensitivity of Typhoon Lingling (2019) simulations to horizontal mixing length and planetary boundary layer parameterizations - Siqi Chen; Feng Xu; Yu Zhang; Guiling Ye; Jianjun Xu; Chunlei Liu (Frontiers of Earth Science, 2022)

Methane in the Yellow Sea and East China Sea: dynamics, distribution, and production - Wangwang Ye; Guanxiang Du; Honghai Zhang; Guiling Zhang (Journal of Oceanology and Limnology, 2022)

Variations in Dissolved Methane in the Yellow Sea During the Spring Algal Blooms of 2009 - Wangwang Ye; Guiling Zhang; Peipei Li; Feng Zhou; Chenggang Liu (Journal of Ocean University of China, 2019)

A novel PTP1b inhibitor vanadium-flavone complex: synthesis and pharmacodynamic evaluation in streptozotocin-induced diabetic mice - Liying Duan; Junwei Ye; Wenlong Sun; Shaoning Wang; Wei-tao Gong; Yuesheng Dong; Guiling Ning (Medicinal Chemistry Research, 2017)